Thiamphenicol and florfenicol combination in Nile tilapia: Simultaneous detection and quantification in plasma and muscle plus skin samples, and pharmacokinetics following single oral administration - Assane, Inácio Mateus [UNESP]; Damaceno, Marina Alves; Campanharo, Sarah Chagas; da Silva, Agnaldo Fernando Baldo; de Sousa, Elielma Lima [UNESP]; do Vale Oliveira, André [UNESP]; de Abreu Reis Ferreira, Daniel [UNESP]; Kotzent, Suzana [UNESP]; de Jesus, Raphael Barbetta [UNESP]; da Paz, Deborah Jacob Freire [UNESP]; Paschoal, Jonas Augusto Rizzato; Pilarski, Fabiana [UNESP] (Elsevier, 2023)
Thiamphenicol (TAP) and florfenicol (FFC) combination has in vitro and in vivo synergistic activity against fish bacterial pathogens. However, a lack of information on its pharmacokinetics (PK) and pharmacodynamics (PD) in fish limits its further application. Therefore, this study aimed to develop and validate analytical methods for simultaneous detection and quantification of TAP and FFC in tilapia plasma and muscle plus skin samples and to determine the PK in freshwater tilapia at 30 ± 0.32 °C after a single oral dose of 5 mg kg−1 TAP +3.75 mg kg−1 FFC. Antimicrobial concentrations were analyzed by HPLC-MS. The PK characteristics were estimated by a non-compartmental model (linear up/log down). Precise, and sensitive methods were developed using ethyl acetate (plasma) and a modified QuEChERS (muscle plus skin) for extraction. Both methods were successfully applied to analyze the plasma and muscle plus skin samples in the PK study. The highest concentrations of TAP and FFC were detected at 0.5 h (6.34 and 3.34 μg mL−1) and 16 h (8.20 and 11.37 μg mL−1) post-administration in plasma and muscle, respectively. There was no significant difference between the peak concentration and apparent volume of distribution during the terminal phase of each antimicrobial in different tissues. However, the peak time, the area under the concentration-time curve, and mean residence time were higher in the muscle, for both antimicrobials (P < 0.05). The calculated PK parameters and the curve obtained for both antimicrobials emphasize their fast absorption and distribution even when used in combination. The results from this study could help establish antimicrobial susceptibility testing interpretative categories and design rational dosing regimens for TAP and FFC combination.
Keywords: Antimicrobials; Bioavailability; Combination therapy; HPLC-MS; Oreochromis niloticus; QuEChERS